MODAL VERBS IN THE UN SECRETARY-GENERAL'S REMARKS ON CLIMATE CHANGE - Edfan Juliansyah; Lia Maulia Indrayani; Ypsi Soeria Soemantri (Fakultas Sastra Universitas Ekasakti, 2020)
This research was conducted to investigate the functions of modal verbs in the UN Secretary-General's remarks on climate change. Qualitative descriptive research design was employed in conducting this research. The benefits of this research are expected to contribute to the development of semantic research regarding modal verbs, and provide the understanding of the functions of modal verbs expressed in response to the climate change. The findings show that the functions of modal verbs expressed in the remarks are certainty, possibility, volition, and obligation. The speaker used the modal verb ‘will’ to express certainty, and volition, while the modal verb ‘must’, and the lexical modal ‘have to’ were used to express obligation. The speaker used the modal verb ‘can’ and the modal verb ‘could’ to express possibility. Based on the results of the research, certainty is the function that was mostly expressed in the remarks, followed by possibility, volition, and obligation. A lot of certainties expressed in the UN Secretary-General's remarks on climate change signifies that the speaker conveyed a lot of predictions or events referring to future time.